Sejarah Perkembangan Kurikulum Pendidikan Bahasa Arab Pesantren Dan Dinamika Metode Pembelajarannya - Tri Pujiati (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2016)
Arabic language learning curriculum has an important role as a milestone of learning in schools. No doubt, the existence of pesantren has spawned a generation that has the ability Arabic, as in Tebuireng salaf pesantren in Jombang. But in reality, the historical development of Arabic language curriculum at the school has not received serious attention in academic circles. As this study aims to find out How did the history, dynamics, and the Arabic language curriculum model viewed from a historical perspective. In view of the movement of history Ibn Khaldun's theory affirms that everything is going to undergo a process of evolution and progress towards a cycle to form a spiral. Meanwhile, Auguste Comte believes that everything is always berprogres oriented progress. Based on studies conducted by the authors can conclude that the curriculum of Arabic language learning in schools Jombang Tebuireng spiral-dialectical. Learning system that is in it massively berprogres on learning madrasah. It is also offset by learning model oriented student centered.